2006
DOI: 10.1190/1.2187760
|View full text |Cite
|
Sign up to set email alerts
|

Induced-polarization measurements on unconsolidated sediments from a site of active hydrocarbon biodegradation

Abstract: To investigate the potential role that indigenous microorganisms and microbial processes may play in altering lowfrequency electrical properties, induced-polarization (IP) measurements in the frequency range of 0.1 to 1000 Hz were acquired from sediment samples retrieved from a site contaminated by hydrocarbon undergoing intrinsic biodegradation. Increased imaginary conductivity and phase were observed for samples from the smear zone (contaminated with residual-phase hydrocarbon), exceeding values obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 42 publications
4
62
1
2
Order By: Relevance
“…Previous experiments showed that SIP responses resulting from biomineralization processes ͑Ntarlagiannis et al, 2005a; Williams et al, 2005;Slater et al, 2007;Personna et al, 2008͒ are significantly higher than SIP responses resulting from microbial activity in the absence of metallic mineral precipitation ͑Abdel Aal et al, 2004;Abdel Aal et al, 2006;Davis et al, 2006͒. Based on such previous experience, we expected that the precipitation of metallic minerals, regardless of the driving processes, would lead to substantial SIP responses.…”
Section: Discussionmentioning
confidence: 94%
“…Previous experiments showed that SIP responses resulting from biomineralization processes ͑Ntarlagiannis et al, 2005a; Williams et al, 2005;Slater et al, 2007;Personna et al, 2008͒ are significantly higher than SIP responses resulting from microbial activity in the absence of metallic mineral precipitation ͑Abdel Aal et al, 2004;Abdel Aal et al, 2006;Davis et al, 2006͒. Based on such previous experience, we expected that the precipitation of metallic minerals, regardless of the driving processes, would lead to substantial SIP responses.…”
Section: Discussionmentioning
confidence: 94%
“…Early geophysical studies that reported higher bulk electrical conductivity and attenuated ground penetrating radar (GPR) signals at LNAPL-contaminated sites were linked to microbial activity associated with biodegradation (e.g., Benson et al 1997;Sauck et al 1998). A large volume of literature now exists supporting the early findings of anomalous geophysical signatures at LNAPL contaminated sites undergoing bioremediation (e.g., Atekwana et al 2000Atekwana et al , 2002Atekwana et al 2004a, b, c, d;Abdel Aal et al 2006;Bradford 2007;Cassidy 2007Cassidy , 2008Allen et al 2007). Attempts to understand the role of microorganisms in altering the physical properties of geologic systems has resulted in the development of a new sub-discipline in geophysics called ''biogeophysics'' ).…”
Section: Introductionmentioning
confidence: 94%
“…Over the past two decades, geophysical techniques have been employed at several LNAPL contaminated sites to characterize both the spatial (e.g., Benson and Stubben 1995;Bermejo et al 1997;Sauck et al 1998;Atekwana et al 2000;2004a;Osella et al 2002;Werkema et al 2003;Tezkan et al 2005;Abdel Aal et al 2006;Sogade et al 2006;Bradford 2007;Cassidy 2007) and temporal (e.g., Lopes de Castro and Branco 2003;Che-Alota et al 2009) extent to understand the evolution of the contamination in the subsurface. Many of these geophysical studies have provided valuable insights into the behavior of LNAPL contamination; however, the results remain mixed.…”
Section: Introductionmentioning
confidence: 99%
“…The growth and metabolic activities of microorganisms are known to alter the chemical and physical conditions of the environment. The biodegradation of hydrocarbons results in the production of bacterial metabolites, including organic acids and CO 2 . Carbonic acid and organic acids such as acetate and fumarate drive mineral dissolution by releasing ions from the sediment grains (18,37,45).…”
mentioning
confidence: 99%
“…Carbonic acid and organic acids such as acetate and fumarate drive mineral dissolution by releasing ions from the sediment grains (18,37,45). Moreover, microorganisms alter their physical surroundings by colonizing sediment surfaces in the form of microcolonies or biofilms or by driving the precipitation of metal sulfides at cell or sediment grain surfaces (1,2,40,57). In addition, the presence of microbial nanowires, which have recently been identified as highly conductive pili on the surfaces of iron-reducing bacteria such as Geobacter (43) and Shewanella (27) species, may also play a role in increasing subsurface conductivity levels in certain geomicrobiological environments.…”
mentioning
confidence: 99%